2019
DOI: 10.1002/jum.15023
|View full text |Cite
|
Sign up to set email alerts
|

Very High‐ and High‐Frequency Ultrasound Features of Cutaneous Larva Migrans

Abstract: Cutaneous larva migrans is a common infestation among travelers. Although the diagnosis may be suspected clinically, cases can show atypical presentations. We present the ultrasound features of 4 cases at 18 and 70 MHz. Small linear hyperechoic and hyper-refringent subepidermal and intrafollicular structures suggestive of fragments of larvae, hypoechoic dermal and hypodermal tunnels that match with dilatation of lymphatic ducts, and inflammatory dermal and hypodermal ultrasound signs can support the diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…[ 1 ] In the recent past, many imaging techniques including dermoscopy have been used in CLM cases to establish the diagnosis and to study the course and depth of penetration of larva in the skin. [ 2 ] Findings of studies identified in the literature regarding the use of various imaging techniques in CLM have been summarized in Table 2 . Our findings of CLM on dermoscopy were more or less the same as that of lymphangioma circumscriptum, supporting the viewpoint of Ogueta I et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ] In the recent past, many imaging techniques including dermoscopy have been used in CLM cases to establish the diagnosis and to study the course and depth of penetration of larva in the skin. [ 2 ] Findings of studies identified in the literature regarding the use of various imaging techniques in CLM have been summarized in Table 2 . Our findings of CLM on dermoscopy were more or less the same as that of lymphangioma circumscriptum, supporting the viewpoint of Ogueta I et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of CLM on dermoscopy were more or less the same as that of lymphangioma circumscriptum, supporting the viewpoint of Ogueta I et al . [ 2 ] that the brown areas observed on dermoscopy correspond to the dilated lymphatic channels and not to the body of the larva. This is further supported by the fact that the use of the lymphatic system has been proposed as one of the paths of dissemination of CLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'image histologique montre la larve enfermée dans le follicule pileux ou dans le derme ou dans l'épiderme ainsi qu'un infiltrat inflammatoire folliculaire et péri-vasculaire lympho-hystiocytaire et une prédominance d'éosinophiles [2,3,10,13,19,21]. Une étude récente de l'image ultrasonographique de LMCA a confirmé la présence de la larve dans le follicule pileux, voire dans le derme et l'hypoderme [11].…”
Section: Discussionunclassified
“…Cependant, des extrêmes ont été rapportés allant d'une heure à 7 mois. La variabilité de cette période d'incubation serait liée selon les auteurs aux facteurs intrinsèques à l'hôte et/ou à l'espèce d'ankylostome en cause [5][6][7]11,15]. La fragilisation de la barrière cutanée due à l'atrophie cutanée et l'immunodépression locale par les dermocorticoïdes contenus dans les produits dépigmentants pourraient expliquer en partie la survenue de la folliculite profuse chez notre patiente en 48 heures.…”
Section: Discussionunclassified